New hominoid fossils from Moroto II, Uganda and their bearing on the taxonomic and adaptive status of Morotopithecus bishopi. Issue 132 (July 2019) - MacLatchy, Laura; Rossie, James; Houssaye, Alexandra; Olejniczak, Anthony J.; Smith, Tanya M.
Abstract: The early Miocene site of Moroto II, Uganda has yielded some of the oldest known hominoid fossils. A new partial mandible (UMP MORII 03'551) is notable for its long tooth row and large, narrow M2 with well-developed cristids - a morphological combination previously unknown for large bodied catarrhines of the Early Miocene and suggesting folivory. The tooth proportions are compatible with belonging to the same taxon as the maxilla UMP 62-11, the holotype of Morotopithecus bishopi ; likewise, the long tooth row and vertical planum of UMP MORII 03'551 suggest that it may represent the same taxon as mandible(s) UMP 66-01 and UMP 62-10. Canine size strongly suggests UMP MORII 03'551 is a female. Comparisons of the tooth crown morphology and tooth row proportions, relative enamel thickness, enamel-dentine junction morphology, long-period line periodicity, and dental wear patterns support significant morphological, developmental, and inferred dietary differentiation, and therefore generic-level distinctiveness, among Afropithecus, Morotopithecus and the Proconsul clade. An isolated M1 (UMP MORII 03'559) is morphologically dissimilar, and much smaller than the actual or inferred size of molars in UMP MORII 03'551, UMP 66-01 and UMP 62-10, supporting the presence of two hominoid taxa at Moroto II, M. bishopi and a smaller bodied proconsulid. Given the high level of body mass dimorphism inferred for Morotopithecus and other early Miocene catarrhines, the known postcrania from Moroto II could be attributable to either taxon. However, UMP MORII 03'551 and the femora UMP MORII 94'80 derive from the same stratigraphic interval, while the isolated M1 was deposited later, increasing the likelihood that the mandible and femora are from the same individual. These new fossils expand our understanding of the taxonomic and adaptive diversity of early Miocene catarrhines.